The choice of surgical treatment method of perforated pyloroduodenal ulcer - D. V. Maksymchuk; V. I. Mamchich; V. D. Maksymchuk (Клінічна хірургія, 2021)
Objective. To develop a method of organ-saving operation aimed at preservation of the physiological function of the pylorus and the normal physiological functioning of the pyloroduodenal area in patients with combined perforated, stenotic pyloroduodenal ulcers.